Therapeutic potential of a drug based on avocado and soy unsaponifiable compounds in the treatment of osteoarthritis: data from Russian and international studies (descriptive review) - A. E. Karateev; A. M. Lila (Современная ревматология, 2022)
Slow-acting symptomatic drugs (SYSADOA) occupy one of the leading positions in the complex treatment of osteoarthritis (OA). These drugs have a symptomatic and structure-modifying effect, while they are well tolerated and rarely cause serious adverse reactions (AEs). This review examines the evidence base for the use of one of the most popular SYSADOAs, avocado-soybean unsaponifiable compounds (ASACs, Piascledine 300).Objective: to provide the most complete analysis of clinical trials of ASACs in OA.Patients and methods. We performed a search in English-language (PubMed) and Russian-language (eLIBRARY.ru) electronic libraries for publications on clinical studies of the efficacy and safety of ASACs in OA. Among the English-language publications were selected: 3 randomized controlled trials (RCTs) of ASACs and their symptomatic effect (n=587), 2 RCTs of the structure-modifying effect of ASACs (n=562), 1 RCT comparing the effect of ASACs and chondroitin sulfate (n=364), and 1 observational study of ASACs in real practice (n=4185). Among the Russian- language publications, 1 observational study of ASACs in real practice (n=6448) and 5 papers containing data from open clinical trials of ASACs (n=356) were found.Results and discussion. According to the results of the presented studies, ASACs have proven efficacy in reducing the intensity of pain and dysfunction in knee OA. There are data confirming the structure-modifying effect of ASACs in OA of the hip joint (HJ). This drug is well tolerated: in RCTs, the incidence of AEs during ASACs and placebo usage was comparable. In observational studies (n=10 634), there were no serious AEs associated with the use of ASACs.Conclusion. There is a robust evidence base for the expediency of the active use of ASACs in knee OA. Given the similarity of the pathogenesis of OA of different localizations, the data of individual successful studies and a favorable safety profile, the use of ASACs can also be considered as a component of the complex treatment of OA of the hip joint, hand joints and spine.